Chromosome breakpoint distribution in nonmelanoma skin cancers - Pavarino, E. C.; Rossit, ARB; Tajara, E. H. (Elsevier B.V., 1997)
We have identified chromosome regions that may be sites of genes activated as a result of chromosomal rearrangements observed in 61 of the 86 skin tumors referenced in the literature. The data showed that most of the breakpoints were distributed throughout the genome and some tended to cluster. Highest frequencies of breakpoints were observed in chromosomes with high relative length, except chromosomes 14 and 15 that were more often affected in malignant tumors, despite their size. Our work provides a starting point for more detailed studies that may allow identification of these genes as important keys in the development and progression of skin cancers. (C) Elsevier B.V., 1997.